Discourses about Venezuelan Migration in Peru: Employment and Working Characteristics - Crespo del Rio, Claudia (2022)
Within the Critical Discourse Analysis framework and through micro-level linguistic tools, we analyze 64 interviews with Peruvians from Lima and Arequipa about the Venezuelan population recently arrived in Peru with the objective of identifying the main representations on labor and working characteristics of migrants. To do so, we interview two groups of people according to their occupation: basic occupation (mainly services) and non-basic occupation (mainly professionals). This criterion is relevant to identify differences in the discourses of the interviewees. Results point out some positive aspects of migrants, such as being hardworking, friendly and attentive to clients, prepared and educated; on the other hand, they also signal negative features, such as stating that they take work away from locals or describing them as lazy, since it is considered that in Venezuela they were not used to work. In the analysis, we observe how these discourses are supported by the contrast with representations of identity within Peruvians, conceived as hard-working and striving. In addition, we note the presence of ideological dilemmas, referring to tensions between contradictory discourses in the same group of interviewees or in the same person.